Design of a compact microstrip patch antenna with a CSRR loaded substrate - Rajakumar Manoj Kumar (2018)
Since the advent of the wireless communications era, microstrip antennas have been used extensively due to their compact planar profile. These antennas are easily mounted to surfaces of aircrafts, satellites making them to be an ideal communicating interface. Microstrip patch antennas are based upon the principles of microstrip line theory and they are generally fabricated on a printed circuit board, due to which the cost of producing microstrip patch antennas are very low. The length of a patch antenna is directly dependent on its operating resonant frequency. The radiating edges of the antenna is approximately equal to half the wavelength corresponding to its resonant frequency. The phase difference of the E-field between the two resonant edges is an integral multiple of the value ‘π’. By the inclusion of a complementary split ring resonating (CSRR) structure to the antenna, the length of the resonating patch can be adjusted independent to the λ/2 constraint, which can lead to decrease in patch size. The objective of this thesis is to study and design a highly compact patch antenna with a CSRR loaded to the antenna structure, validate the results through theoretical simulations and then practically verify the results after fabrication. From the analysis of various CSRR structures, an optimal design methodology for size reduction will be attempted. The proposed structure is designed to radiate at 2.45 GHz. The methodology proposed in this thesis can be made use in the design of antennas with resonant frequencies in the other ranges as well. All the antenna designs showcased in this study were designed and theoretically verified through the Computer Simulation Technology studio suite using the Microwave and RF module. By simulating the final antenna structure, it is observed that it radiates at 2.45 GHZ with gain 5.71 dB. The fabricated antenna upon testing displays a shift in resonant frequency to 2.80 GHz with gain 3.31 dB due to the presence of air gap between the composite substrate structure.